Cucumber-Derived Exosome-like Vesicles and PlantCrystals for Improved Dermal Drug Delivery - Abraham, Abraham M.; Wiemann, Sabrina; Ambreen, Ghazala; Zhou, Jenny; Engelhardt, Konrad; Brüßler, Jana; Bakowsky, Udo; Li, Shu-Ming; Mandic, Robert; Pocsfalvi, Gabriella; Keck, Cornelia M. (Pharmaceutics, 2022)
(1) Background: Extracellular vesicles (EVs) are considered to be efficient nanocarriers for improved drug delivery and can be derived from mammalian or plant cells. Cucumber-derived EVs are not yet described in the literature. Therefore, the aim of this study was to produce and characterize cucumber-derived EVs and to investigate their suitability to improve the dermal penetration efficacy of a lipophilic active ingredient (AI) surrogate. (2) Methods: The EVs were obtained by classical EVs isolation methods and by high pressure homogenization (HPH). They were characterized regarding their physico-chemical and biopharmaceutical properties. (3) Results: Utilization of classical isolation and purification methods for EVs resulted in cucumber-derived EVs. Their dermal penetration efficacy for the AI surrogate was 2-fold higher when compared to a classical formulation and enabled a pronounced transdermal penetration into the viable dermis. HPH resulted in submicron sized particles composed of a mixture of disrupted plant cells. A successful isolation of pure EVs from this mixture was not possible with classical EVs isolation methods. The presence of EVs was, therefore, proven indirectly. For this, the lipophilic drug surrogate was admixed to the cucumber juice either prior to or after HPH. Admixing of the drug surrogate to the cucumber prior to the HPH resulted in a 1.5-fold increase in the dermal penetration efficacy, whereas the addition of the AI surrogate to the cucumber after HPH was not able to improve the penetration efficacy. (4) Conclusions: Results, therefore, indicate that HPH causes the formation of EVs in which AI can be incorporated. The formation of plant EVs by HPH was also indicated by zeta potential analysis.